A predictive model for salt intrusion in estuaries applied to the Muthupet estuary (India) and Bouregreg estuary (Morocco). Issue 4 (1st October 2020) - Haddout, S.; Priya, K.L.; Adarsh, S.
ABSTRACT: In this paper, two 1D salt intrusion models, i.e. the steady-state and unsteady-state salinity intrusion model are used to assess the salt intrusion distribution in Muthupet estuary, a Ramsar site in Tamil Nadu, India; and Bouregreg estuary, in north-western part of Morocco. Results indicate that the steady-state salt intrusion model performs well to salinity observations especially during post-monsoon period (Indian estuary). Despite the fact that the high-salinity values observed during pre-monsoon period at a distance of 5 km to 7.5 km from the mouth are badly represented by the steady-state model it is a good indicator for the salt intrusion length. Additionally, this research shows that it is likely that an additional source of salt is causing the increase in salinity values at Lagoon reach and that the unsteady-state salt intrusion is able to represent this. On the other hand, a normal estuary is presented in this paper, for study comparison, i.e. Bouregreg estuary. The steady-state salt intrusion model outperformed the model results of the Indian estuary and is better to predict salt intrusion length and salinity variation along the Bouregreg estuary.